International Public Relations methods in building the state's image through Cyberspace - Abbas, Saja Khudir; Aleqabi, Jassim Tarish (ALBAHITH ALALAMI, 2021)
The researcher has studied in his research (International Public Relations methods in building the state's image through Cyberspace), analytical study of the Facebook and twitter pages for British foreign office , the role was played by the International Public Relations in building the mental image of British , especially after the new media and internet have became influential role in political life . and became an important tools used by political institutions as ministries of foreign affairs in the twenty: one century .The researcher identified the problem of this study with the following question:(what is the role of the International Public Relations in building the mental image of state through Cyberspace)To answer this question , the researcher identified a set of objectives at based on analytical study , the important British foreign office on social media for building the mental image of British.The researcher used survey method as descriptive study was used the content analysis to collection of information.